Effect of Secang Drink (Caesalpinia Sappan L.) on Plasma Nitric Oxide Level and Blood Pressure in Prehypertension Peoples - Januariyatun, A; Wahyuningsih, M S H; ., Susetyowati (KnE Life Sciences, 2019)
The is experimental with pre-post test control group design. This study aimed to know the effect of second drink on the plasma NO (Nitric Oxide) level and blood pressure in an officer with prehypertension. The subjects were 36 officers at Balaikota Yogyakarta Indonesia aged 25-45 years that divided into two groups: the intervention group who was given second drink (3.8-gram second in 200 mL of water) for four weeks and a control group who not given second drink. Plasma NO level was measured using the Griess method and blood pressure were measured using a mercury sphygmomanometer. There were no significant differences between intervention and control group (p>0.05) of plasma NO level increase (2.69 (-10.69-25.29) µmol/L versus 2.32(-7.65-18.48) µmol/L), systolic blood pressure decrease (4.20±7.27 mmHg versus 3.95±7.08 mmHg) and diastolic blood pressure decrease (4.99±9.12 mmHg versus 4.46±8.62 mmHg). In summary, secang drink could increase plasma NO level and decrease blood pressure but not significant compared to the control group. Further research is needed to prove this result. Keywords: prehypertension, secang drink, Caesalpinia sappan L., nitric oxide, blood pressure